PERANCANGAN INFOGRAFIS KOTA/KABUPATEN DI JAWA TENGAH DI GRAND MAERAKACA SEMARANG - Syaefudin, Mohamad; Atno, Atno; Srianto, Srianto; Kumara, Alex; Makarim, Bill Haq; Istiqomah, Putri Wahyuningsih (Universitas Sanata Dharma, 2025)
The opportunity for educational travel in Grand Maerakaca Semarang requires enhancement to boost its competitiveness. Although it has been established for more than three decades, some educational content needs to be added, considering that the building/site display is not yet informative enough for visitors. The addition of information displays regarding areas/tourism/economic potential will improve the position of Grand Maerakaca as an educational recreation park regarding regions in Central Java, which is very strategic for community learning. The community service team designed content and infographic displays for cities/regencies in Central Java. The presence of this infographic adds information on tourism potential and the uniqueness of cities in Central Java. This community service activity resulted in the design of 65 infographic posters from 35 cities/regencies in Central Java. The management of the Grand Maerakaca tourist park expressed appreciation to the team for adding infographics at the city/regency pavilion and expected it to increase visitors for educational tourism.